1972
DOI: 10.1002/pol.1972.150100216
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of urethane model systems

Abstract: The photo‐oxidation products of ethyl N‐phenyl‐carbamate (EPC) were identified as ethyl o‐aminobenzoate, ethyl p‐aminobenzoate, aniline, water, carbon dioxide, azo compounds, and other colored material. The ethylaminobenzoates, formed by intramolecular rearrangement of EPC, were precursors of the azo and colored products. Diethyl 4,4′‐azobenzenedicarboxylate was produced by the ultraviolet irradiation of the precursor, ethyl p‐aminobenzoate, in the presence of oxygen. Benzophenone and anthraquinone, as the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…The data show that variations in absorbance at 400 nm are highly dependent on the presence of oxygen, a phenomenon that could be explained by the formation of azo compounds derived from the secondary photolysis of photo-oxidation of aromatic amines when oxygen is present. 8 The observed changes in reduced viscosity and UV absorbance are consistent with a two-step mechanism for the photolysis of bisphenol-based polyurethanes.…”
Section: Influence Of Oxygen and Nitrogen On Viscositysupporting
confidence: 71%
See 1 more Smart Citation
“…The data show that variations in absorbance at 400 nm are highly dependent on the presence of oxygen, a phenomenon that could be explained by the formation of azo compounds derived from the secondary photolysis of photo-oxidation of aromatic amines when oxygen is present. 8 The observed changes in reduced viscosity and UV absorbance are consistent with a two-step mechanism for the photolysis of bisphenol-based polyurethanes.…”
Section: Influence Of Oxygen and Nitrogen On Viscositysupporting
confidence: 71%
“…Using an analogy based on studies of aryl monocarbamate compounds such as ethyl N-phenylcarbamate, 8 -11 it has been implied that MDI-based polyurethanes photodecompose, at least to some extent, by a photo-Fries rearrangement process (Scheme 1). Beachell and Chang 8 concluded that photolysis of the primary photo-Fries products (as well as cleavage-type products) in the presence of oxygen yielded colored azo compounds which were responsible for the discoloration seen in polyurethanes. Thus the photolysis of MDI-based polyurethane, according to Beachell and Chang, proceeds in two-steps: (1) the formation of primary aromatic amine products, and (2) photo-oxidation of these products to colored azo compounds.…”
Section: Introductionmentioning
confidence: 98%
“…Aromatic polyurethanes rapidly degrade and undergo yellowing on exposure to UV light [1,2], whereas the more expensive aliphatic polyurethanes show better photo resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on model compound studies, Beachell and Chang (14) concluded that both MOI and TDI based polyurethanes photodegrade in part by a photo-Fries rearrangement process (Scheme II). In the present investigation, the effect of polymer crystallinity and flexibility on the photolysis process, as revealed by both fluorescence and percent gel formation, will be measured.…”
Section: Introductionmentioning
confidence: 99%
“…This, of course, severely limits their use in situations which require even moderate exposure to sunlight. As a consequence, considerable attention has been given over the past two decades to the study of the photodegradation process of aromatic diisocyanate based polyurethanes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%